The disordered- and ordered-state structures of κ-carrageenan : an X-ray scattering, molecular dynamics, and density-functional theory study : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Physics at Massey University, Palmerston North, New Zealand - Westberry, Benjamin (Massey University, 2022)
κ-carrageenan is a biopolymer extracted from marine algae. It exists in aqueous solution, at high temperatures and/or low salt concentrations as a ‘disordered-state’, and at low temperatures and in the presence of certain salts as an ‘ordered-state’. The transition between disordered- and ordered-states involves molecular structural changes, which are essential to its interesting viscoelastic properties that are routinely exploited in a plethora of applications. Despite this, the molecular conformations of the disordered- and ordered-states, as well as the details of the transitional pathway connecting them, remain a source of contention. While decades of research have amassed a vast trove of information on the disorder-order transition, an atomistic understanding of the structure in solution has remained elusive. This study takes advantages of recent advances in computational capabilities in order to simulate κ-carrageenan solutions on length scales of ∼10 nm over μs time scales, and thus develop atomistic models of the disordered- and ordered-states. Both models are used to calculate wide-angle X-ray scattering profiles, and these are subsequently validated by comparison to data obtained at a synchrotron facility. The models will be further explored using density functional theory to calculate their expected optical rotation behaviour, which finds that the formation of double-helices from single chains is able to explain the increase in optical rotation measured experimentally when transitioning from the disordered to ordered-state. Structural analysis of both experimentally-verified models find the disordered-state to have a significant amount of residual helical secondary-structure, whereas the ordered-state is mostly double-helical. Crucially, simulations show that the ordered-state arises spontaneously from the so-called disordered-state at a rate dependant on salt concentration, without prior uni-molecular changes. The findings of this research are the most detailed model of the disorder-order transition to-date, and demonstrate that the existing paradigm of a ‘coil-to-helix’ transition is in need of revision.
Listed in 2023 Dean's List of Exceptional Theses
Keywords: Biopolymers; Structure; Marine algae; Order-disorder models; X-rays; Scattering; Density functionals; Dean's List of Exceptional Theses; 510403 Condensed matter modelling and density functional theory